Characteristics of the vertical distribution of tropospheric ozone in late autumn at Yangjiang station in Pearl River Delta (PRD), China. PartⅠ: Observed event. (1st January 2021) - Zhang, W.; Zou, Y.; Zheng, X.D.; Wang, N.; Yan, H.; Chen, Y.P.; Zhao, X.J.; Ji, Z.P.; Li, F.; Mai, B.R.; Yin, C.Q.; Deng, T.; et al.
Abstract: Ozone has become the main factor affecting the air quality in the Pearl River Delta (PRD) in recent years, and a clear understanding source of ozone pollution is a top priority of ozone pollution prevention. However, the vertical distribution of tropospheric ozone in the PRD is poorly understood. Based on daily ozone sounding data obtained in Yangjiang (111°58'00" E, 21°50'00" N), Guangdong Province, from 18 November tjo 3 December 2013, the detailed vertical distribution of tropospheric ozone and its influencing factors were determined and compared with weekly autumn ozone profile data obtained at the Hong Kong Observatory (HKO) and corresponding tropospheric column ozone (TCO) datasets from the Ozone Monitoring Instrument (OMI) and Microwave Limb Sounder (MLS) onboard satellite AURA. Overall, the ozone profiles observed in Yangjiang are in accordance with those of the HKO in terms of the vertical structure. The TCO values are 34.2 ± 4.0 and 34.3 ± 4.6 DU, respectively, that are, 4 DU higher than those of satellite data, indicating that the OMI/MLS product underestimates the TCO level in the PRD region. The Yangjiang ozone profiles indicate significant variations in the ozone vertical structure and concentration during the observation period. A significant ozone peak permanently occurs in the lower troposphere at 1.1 ± 0.4 km above the surface. The vertical structural difference is mainly reflected in the presence of low-ozone strata (below 30 ppbv) near the tropopause and ozone peaks and high-ozone stratification in the middle and upper troposphere. The average ozone peak concentrations in the lower, middle, and upper troposphere are 65.2 ± 9.9, 57.8 ± 7.7, 71.8 ± 13.6 ppbv, respectively, which are higher than the average ground-level ozone concentration (48.9 ± 9.4 ppbv). Based on the analysis of the profile characteristics, weather conditions, and backward trajectories, it can be concluded that the low-ozone strata near the tropopause are caused by the regional transport of the tropical air mass from the tropical cyclone storm area. Potential vorticity analysis shows that stratosphere-troposphere exchange (STE) is the main reason for the formation of the ozone peaks and its varying concentrations in the middle and upper troposphere. Photochemical reactions represent the main factor affecting the ozone concentration in the lower troposphere. The STE is also an important factor affecting the ozone in the lower troposphere, leading to an increase in the surface ozone concentration by 10.9 ppbv. Graphical abstract: Image 1 Highlights: The vertical distribution of tropospheric ozone at Yangjiang are firstly presented. Tropical cyclone storm result in low ozone strata in the upper troposphere. STE is the main factor causing the ozone peak in the middle and upper troposphere. The contribution of stratospheric O3 to surface O3 is about 10.9 ppbv.